The Influence of Environmental Sanitation, Clean Water Access, and Hygiene Behavior on Stunting Incidence: A Community-Based Public Health Study - Gusman, Gusman (PT. Anagata Sembagi Education, 2026)
Stunting remains a major public health challenge in many developing countries and reflects long term nutritional deficiencies combined with environmental and behavioral determinants affecting child growth. In addition to inadequate dietary intake, environmental sanitation, access to clean water, and hygiene behavior are increasingly recognized as critical factors influencing stunting incidence among children under five years of age. This study aims to analyze the influence of environmental sanitation, clean water access, and hygiene behavior on the occurrence of stunting within a community based public health context. The study employed a quantitative cross sectional design involving households with children under five years old. Data were collected through structured questionnaires, environmental observations, and anthropometric measurements based on the World Health Organization Child Growth Standards. Data analysis included descriptive statistics, chi square tests, and logistic regression to identify significant determinants associated with stunting incidence. The results indicate that poor environmental sanitation, limited access to clean drinking water, and inadequate hygiene practices are significantly associated with increased risk of stunting. Children living in households with inadequate WASH conditions are more vulnerable to repeated infections such as diarrhea and intestinal diseases, which impair nutrient absorption and growth. In conclusion, improving environmental sanitation, ensuring access to safe drinking water, and strengthening hygiene behavior are essential public health strategies to reduce stunting prevalence and promote healthy child development..